Consumer Preferences in South Tangerang's Residential Housing Market: A Study of Price, Quality, and Location Factors - Windarko, Windarko; Salsabil, Syifa Hanifa; Lastro, Djano (Westscience Press, 2025)
This study investigates the key factors influencing housing purchase decisions in South Tangerang's growing property market, with a focus on price, construction quality, and location. The increasing urban development in South Tangerang necessitates a deeper understanding of these factors to meet the rising housing demand. Utilizing a quantitative approach, data was collected from 142 homebuyers in 2023, with 118 respondents selected through purposive sampling. The primary data was gathered via structured online questionnaires, ensuring reliability and normal distribution. The analysis revealed that price and location significantly impact purchase decisions, while construction quality does not. The findings highlight the importance of considering price and location in shaping consumer preferences, offering valuable insights for developers to enhance their strategies and effectively address market demand in this dynamic sector.